2017
DOI: 10.4081/ija.2017.928
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sowing time, hybrid and environmental conditions on the contamination of maize by emerging mycotoxins and fungal metabolites

Abstract: Mycotoxins and other fungal metabolites represent the most insidious safety risks to cereal food and the feed chain. Optimising agronomic practices is one of the main strategies adopted to minimise the contents of these undesirable substances in grain-based commodities. The aim of this study was to investigate the effect of the combination of sowing times and hybrids on the occurrence of emerging mycotoxins and fungal metabolites in maize. Field experiments were carried out in 2 sowing times (early vs late) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 28 publications
5
30
0
Order By: Relevance
“…Similar to our results, Blandino et al (2017) have also established that FBs and DON levels in maize grains influenced by the type of the hybrids from FAO 500 and 600 maturity groups and environmental conditions. In addition, Van Rensburg et al (2016) concluded that seven South African maize genotypes were differed in susceptibility to natural fungal and FBs contamination.…”
Section: Graphic 1 Mean Monthly Temperatures Total Monthly Rainfallsupporting
confidence: 92%
See 3 more Smart Citations
“…Similar to our results, Blandino et al (2017) have also established that FBs and DON levels in maize grains influenced by the type of the hybrids from FAO 500 and 600 maturity groups and environmental conditions. In addition, Van Rensburg et al (2016) concluded that seven South African maize genotypes were differed in susceptibility to natural fungal and FBs contamination.…”
Section: Graphic 1 Mean Monthly Temperatures Total Monthly Rainfallsupporting
confidence: 92%
“…The incidence of Fusarium species on the maize grains was similar to the reported data of De Curtis et al (2011) and Covarelli et al (2011). Analyzing the susceptibility of three maize hybrids to Fusarium and FBs contamination, in Southern Italy, De Curtis et al (2011) have isolated F. proliferatum (up to 81.5%) and F. verticillioides (up to 26.5%) as the predominant fungal species in both investigated years (2005)(2006).…”
Section: Graphic 1 Mean Monthly Temperatures Total Monthly Rainfallsupporting
confidence: 84%
See 2 more Smart Citations
“…However, we already established for aflatoxins alone that no clear association was found between aflatoxin prevalence and season, in a tropical country such as Costa Rica (Granados-Chinchilla et al 2017). Although this contrasts with findings in other countries with more defined seasons for feed and ingredients alike (Abdou et al 2017;Blandino et al 2017). Furthermore, prediction of toxin behavior and seasonal variations are more challenging due to climate change (van der Fels-Klerx et al 2016a).…”
Section: Mycotoxin Seasonalitymentioning
confidence: 89%